Synthesis of functional zinc layered hydroxide and its organic-inorganic nanohybrids - Mohd Zobir, Hussein; Zulkarnain, Zainal; Siti Halimah, Sarijo'; Norhayati, Hashim; Mohammad Yeganeh, Ghotbi; Mohd Zaki, Abd Rahman (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.